Pengaruh Struktur Asset, Growth Opportunity, dan Profitabilitas Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Rahmadhani, Intan; Yeni, Fitri; Sanjaya, Sigit (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
The purpose of the research conducted is to find out how much influence asset structure, growth opportunity, and profitability have on capital structure with company size. The population used in the research carried out was 214 companies in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) in 2018-2022 obtained from www.idx.co.id, using porposive sampling techniques and obtaining a total of 59 manufacturing sector companies as samples. The results of the study indicate that asset structure and growth opportunity on capital structure have a positive and significant effect on capital structure, profitability partially has a negative and significant effect on capital structure, company size is able to moderate the effect of asset structure, growth opportunity, and profitability on capital structure in manufacturing sector companies listed on the Indonesia Stock Exchange.